Analysis and Development of Education and Training Management Information Systems at the Jambi Province Human Resources Development Agency - Bramana Jaya Safutra (Jurnal Prajaiswara, 2020)
The Jambi Province Human Resources Development Agency has created a training information system in an effort to manage human resource management in regencies, cities and throughout the province of Jambi. However, along with the implementation of the use of this training system, several problems were still found in the use of the system, both from the apparatus in the BPSDM agency and the apparatus as training participants. There are some obstacles to the implementation of the system, such as the lack of consistency of the organizing committee in using the education information system on the grounds that it is still difficult to understand the interface pattern in the application system, so the committee is reluctant to input data and use the application system as a registration facility for training participants. So in the implementation of activities, there are often errors in data and information of training participants which result in errors in the training implementation report. To solve this problem, the researchers conducted an analysis and development of the education management information system at the Jambi Province Human Resources Development Agency with the aim of making users it easier forto easily understand the use of these web-based applications.